A quantidade de mata como principal influência em bandos mistos de aves de Mata Atlântica fragmentada - Silva, Marina Isidoro [UNIFESP] (2015)
Forest fragmentation and habitat loss are considered the major threats to biodiversity. Studies of the effects of these processes on the species should also include landscape analysis rather than just local analysis as in many studies. Among several possible landscape metrics, the landscape habitat amount has been highlighted and, in many studies, is considered as the most important for species persistence and environmental processes. Therefore, this study aimed at testing the effects of landscape forest amount on Atlantic Forest mixed-species bird flocks. Mixed flocks are associations of two or more species that interact for a time, space and direction and the survival of many species depends on this system. Changes in the forest amount could affect the mixed flocks negatively, thus the hypothesis of the study is that in landscapes with higher forest amount the flocks would be more frequent, larger and with higher species diversity. We selected seven landscapes in order to form a gradient of forest amount. In addition to this variable we also tested the effects of the size of the focal patch, the distance (isolation) of forest fragments and landscape diversity (heterogeneity) on the mixed flocks. To analyze our results we used the method of Generalized Linear Models (GLM) and subsequent selection of the most parsimonious models through the Akaike Information Criterion corrected for small samples. This study showed that forest amount is the landscape characteristic that exerts the greatest effect on the frequency, size and species richness of mixed flocks, being positive the relationship between these variables. Beyond the forest proportion, the distance of the forest patches also positively influenced the frequency of flocks. Regarding the flocks size and richness, multiple models have been selected, and the forest proportion was present in all of them. The other variables had a weak influence on these parameters. In combination with the forest proportion in multiple models, fragment size and landscape diversity influenced the flocks negatively and the distance, positively. These results are consistent with the habitat amount hypothesis and reinforce the importance of employing landscape metrics in ecological studies. The importance of forest amount for mixed flocks reflects how this variable is essential for the conservation of several bird species, for many of them depend on this system and its disappearance may lead to local extinction of these species.